PENGARUH LAMA PERENDAMAN ZAT PENGATUR TUMBUH ALAMI AIR CUCIAN BERAS TERHADAP PERTUMBUHAN TANAMAN SAMBUNG NYAWA (Gynura procumbens) DENGAN METODE STEK BATANG - Salsabilla Putri, Ambar; Tyastirin, Esti (Jurnal Biogenerasi, 2025)
This study aims to determine the effect of natural Plant Growth Regulators (PGR) from rice washing water on the growth of grafting plants through the stem cutting method. The research method used in this study was a Completely Randomized Design (CRD) consisting of 3 treatments and each treatment was repeated 8 times. The experiments carried out were as follows: P1 (control, without soaking in PGR rice washing water), P2 (soaking for 10 minutes in PGR rice washing water), and P3 (soaking for 20 minutes in PGR rice washing water). The parameters observed included plant height, number of leaves, and leaf area. The results showed that the treatment of soaking for 10 minutes in natural PGR rice washing water was the best treatment because the average value for the number of leaves tended to be high and affected the leaf area. The control treatment (without soaking) produced the highest plants. Soaking for 20 minutes (P3) tended to only increase the average growth value for each parameter each week.